In Vivo and Clinical Studies of Sea Cucumber-Derived Bioactives for Human Health and Nutrition From 2012-2021 - Liang, Qi; Ahmed, Faruq; Zhang, Miansong; Sperou, Niki; Franco, Christopher M. M.; Feng, Qianjin; Zhang, Wei (Frontiers in Marine Science, 2022)
Sea cucumbers are amongst the highest value seafoods available commercially, especially in the south-east Asian region, primarily due to their nutritional and health benefits as applied in Traditional Chinese Medicine. While the majority of studies for nutritional products derived from sea cucumber compounds have been conducted in vitro, the number of in vivo and evidence-based human clinical studies are limited. This review has critically assessed the advances in in vivo and clinical studies of sea cucumber-derived bioactives (both extracts and compounds) via a comprehensive literature research on papers published in the last ten years from 2012-2021. Sea cucumber-derived compounds were reported to have the following activities: anticancer, antihyperlipidemic, antihyperglycemic, anti-inflammatory, anticoagulant/antithrombotic, antioxidant, and antihypertension, immunomodulatory, wound healing and as treatments for Alzheimer’s and Parkinson’s diseases. These active compounds include triterpene glycosides (saponins), fucosylated chondroitin sulfate (FCS), cerebrosides, glycosaminoglycan, fucoidan, phospholipids, polysaccharides, peptides, long-chain bases, Frondanol A5, acid mucopolysaccharide, and phosphatidylcholines. Gaps, challenges and future directions have been identified and discussed separately to progress different areas of research and to further scientific validation, development and application of sea cucumbers for human health and nutritional products.